Holistic Educational Philosophy Ideas in Waldorf Education by Rudolf Steiner - Agung Nurcholis (At-Ta'dib, 2021)
This paper presents Rudolf Steiner's idea of Waldorf Education as an alternative to modern educational principles that can be used. In its implementation, Steiner started his philosophy of education starting from anthroposophy which can be understood as the antithesis of anthropocentric. Anthroposophy views that humans must see themselves as a whole, unite with the universe and carry out self-searches to reach self-perfection at the level of wisdom. There are four main ideas; Spiritual knowledge and freedom, Nature of Human beings, Evolution-Emanation, and ethics. In the technical implementation, holistic education has three principles; connectedness, inclusion, and balance. This paper will also describe the general principles and some specific principles in Waldorf Education, about the characteristics of the curriculum, how to treat students, and how to become a Waldorf teacher. As well as a brief description of the architectural significance of school buildings in Waldorf schools. This idea of Steiner's educational philosophy contains many interesting and potentially useful ideas, although not a few consider them to be contrary to today's modern educational models.